2021
DOI: 10.1007/s40120-021-00304-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Demographics, Triptan Contraindications, and Prescription Patterns of Patients with Migraine: A German Claims Database Study

Abstract: Introduction: Migraine is a neurological disease with a considerable economic and societal burden that negatively impacts quality of life and productivity. Triptans are potent serotonin receptor agonists widely used to treat migraine attacks. Little is known about German patients with migraine diagnosed with triptan contraindications or those who discontinue triptans. Methods: This retrospective observational study identifies adults with migraine from a German sickness fund database (2010)(2011)(2012)(2013)(20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…and in hemiplegic migraine and migraine with brainstem aura (4,42). As migraine, mainly with aura, is linked to a wide range of ischemic vascular disorders including myocardial infarction and ischemic stroke, contraindications may be relevant in some migraine patients (42)(43)(44)(45). Based on a retrospective analysis among commercially insured adults in the US, contraindications for triptans were reported in up to 20% of migraine patients.…”
Section: Triptansmentioning
confidence: 99%
“…and in hemiplegic migraine and migraine with brainstem aura (4,42). As migraine, mainly with aura, is linked to a wide range of ischemic vascular disorders including myocardial infarction and ischemic stroke, contraindications may be relevant in some migraine patients (42)(43)(44)(45). Based on a retrospective analysis among commercially insured adults in the US, contraindications for triptans were reported in up to 20% of migraine patients.…”
Section: Triptansmentioning
confidence: 99%
“…Using administrative data among patients with migraine in Germany from 2010 to 2018, extrapolation to the general German population was performed 18 . Of the patients with migraine, 14.5% had contraindications to triptan medication, most commonly history of stroke or transient ischemic attack (6.1%), and contraindications were more common with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Germany from 2010 to 2018, extrapolation to the general German population was performed. 18 Of the patients with migraine, 14.5% Potential reasons why providers prescribe medications for patients with contraindications include not investigating if the patient has contraindications and not knowing the contraindications for the medication. 24 In the Acute Migraine Triptan Guidelines, the American Headache Society suggests evaluating for risk factors, such as coronary heart disease, diabetes, obesity, severe uncontrolled hypertension, or hypercholesterolemia, before prescribing triptans.…”
Section: Using Administrative Data Among Patients With Migraine Inmentioning
confidence: 99%
“…In this study, the serum levels of ALB, TBIL, CRE, and UA were significantly lower in the migraine group than in the HC group, indicating an association between oxidative stress and migraine. Several epidemiological studies on migraine have demonstrated that the prevalence of migraine in women is higher than in men ( 30 ). As shown in Table 4 , by the sex subgroup analysis, the serum CRE and ALB levels of female patients were lower than those of male patients, suggesting weaker antioxidant capacity in women, which may provide a new perspective for explaining the higher incidence of migraine in women.…”
Section: Discussionmentioning
confidence: 99%